Long-Term efficacy and safety analysis of secukinumab in the treatment of pediatric generalized pustular psoriasis: a real-world study - Lu Xing; Lingsheng Long; Tao Wu; Lingrui Yin; Li Yu; Jingnan Wu; Danchen Li; Limin Miao; Hong Shu (Journal of Dermatological Treatment)
Purpose: To evaluate the long-term efficacy and safety of secukinumab in pediatric patients with generalized pustular psoriasis (GPP).Materials and methods: A retrospective study was conducted from July 2021 to July 2024, including 10 children with GPP. Patients were divided into two age groups: children aged 0–3 years received 75 mg of secukinumab, while those aged 3–12 years received 150 mg. Secukinumab was administered subcutaneously at weeks 0, 1, 2, 3, and 4, followed by maintenance every 4 weeks. Treatment response was evaluated using the Generalized Pustular Psoriasis Area and Severity Index (GPPASI), Japanese Dermatological Association (JDA) score, and Infants’/Children’s Dermatology Life Quality Index (IDLQI/CDLQI).Results: By week 1, all patients achieved GPPASI-50 and mild JDA scores. By week 2, eight patients reached GPPASI-100, and nine achieved JDA scores of 0/1. Between weeks 12 and 70, all patients maintained GPPASI-100 and JDA scores of 0. Minimal relapses occurred in four patients, and one experienced five flares. The mean IDLQI/CDLQI improved from 21.8 at baseline to 0.4 by week 4, with sustained improvements throughout.Conclusions: Secukinumab demonstrated long-term efficacy and safety in pediatric GPP, significantly improving clinical outcomes and quality of life, with no serious adverse events reported.